BIOSORPSI LOGAM OLEH BAKTERI - Muhammad Harry Rahmadan; Rudi Kartika; Rahmat Gunawan (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
The growth of industry in Indonesia, especially in the textile sector, has led to an increase in the production of liquid waste containing heavy metals such as chromium (Cr), lead (Pb), and copper (Cu). These metals can pose significant health risks if they enter the body of living things. To overcome this, one alternative method of reducing liquid waste is to utilize biosorption by bacteria. This study aims to determine the ability of metal absorption by several bacteria, namely Streptococcus mutans, Flavobacterium sp, Pseudomonas sp, and Bacillus subtilis. The results showed that Streptococcus mutans was able to absorb Cr (VI) with a maximum efficiency of 90.80% at a concentration of 5 ppm on the 5th day. While Flavobacterium sp was able to absorb Pb at a maximum of 96% at a concentration of 2 ppm on the 18th day. Pseudomonassp showed maximum uptake of 96.192% for Cr(VI) at 5 ppm on day 14, 36.874% for Pb at 4 ppm on day 16, and 84.447% for Cu(II) at 3 ppm on day 16. Bacillussubtilis showed maximum uptake of 97.42% for Pb at 10 ppm. These findings indicate that bacteria have significant potential for heavy metal biosorption in wastewater treatment. Keywords: Absorption,Metal,Bacteria